Hematological changes in experimentally infected doges with Salmonella give: F.G. Habasha M.S. Aziz , Taha Yassin Ghani - Aziz, F.G. Habasha M.S. (The Iraqi Journal of Veterinary Medicine, 2009)
Hematological changes in experimentally infected dogs with Salmonella give were studied in 8puppies aged 8-9 weeks. They were separated equally into two groups. The first group has been infected with 4.8xCFU with Salmonella give , while the second group was used as control. Hematological changes were 9 10characterized by an increase in P.C.V. , Hb , ’RBC count ,TPP and fibrinogen , while there was no significantchanges in MCV ,MCH , MCHC . The total leukocytic count was increased during the two days and then graduallydecreased at the end of the experiment